Repairing Cell Structure of Jejunum Tissue in RA-CFA Rat Model Improved by Caprine CSN1S2 Protein - Zaidah, Laili Nur; Soewondo, Aris; Fatchiyah, Fatchiyah (Graduate School, Universitas Brawijaya, 2020)
We aimed to analyze the effect of CSN1S2 protein in Etawah crossbred goat milk and yogurt on the histopathology of the jejunum and the amount of cell damage in Complete Freund's adjuvant (CFA)-induced rheumatoid arthritis (RA) rats. The rats were divided into six groups: the untreated control rats (C), control rats were given CSN1S2 protein from Etawah crossbred goat milk (CM) or yogurt (CY), RA rats, RA rats given CSN1S2 protein from Etawah crossbred goat milk (RAM) or yogurt (RAY). Hematoxylin-eosin staining was conducted for the histopathological analysis of jejunum. Statistical analysis was done using one-way ANOVA (a significance value of p ≤ 0.05) followed by the Tukey test. Our study observed that the control, CM, and CY group have a normal histological structure of jejunum. The damage to the jejunum structure was reported in the RA group. The milk CSN1S2 protein was able to improve the structure of jejunum villi and increase the normal cell number in the jejunum of the RA group, similar to control. The RAY group showed an impaired jejunum structure and a high number of necrotic cells as in the RA group.